Effective piezoelectric energy harvesting using beam plucking and a synchronized switch harvesting circuit. (12th July 2018) - Fu, Hailing; Yeatman, Eric M
Abstract: Piezoelectric energy harvesting, as a way to convert kinetic energy into electricity for low-power electronics, has drawn great attention for the last decade. However, issues still remain, including narrow operating bandwidth and low harvesting capability. In this paper, beam plucking (frequency up-conversion) and a parallel synchronized switch harvesting on inductor (P-SSHI) circuit are integrated in a piezoelectric energy harvester to improve the energy harvesting capability over a wide operating bandwidth. A theoretical model for the plucked beam is established using a distributed-parameter method. In order to study the system dynamics, an equivalent circuit for the plucked beam is built to integrate with the P-SSHI circuit. System dynamics, including the input power, beam tip displacement and output power, are investigated for different driving frequencies and load resistance. The plucked beam provides a uniform and single-frequency vibration for the P-SSHI to generate reliable switching events for any low-frequency wideband vibration; the P-SSHI circuit exhibits an improved electrical damping ratio which is beneficial to alleviating the power fluctuation issue for plucked beams at high frequencies. An experimental validation was conducted, and a close match was obtained. Enhanced output power with low power fluctuation was obtained in the plucked beam and P-SSHI circuit configuration over a wide frequency bandwidth with constant load resistance.